Deliberation-Without-Attention in Solving Insight and Analytic Problems: Does Distractor Type Have an Effect? - Tidikis, Viktoria; Stenson, Anthony (Psichologija, 2023)
Replication failure is at the heart of criticism of Dijksterhuis’ unconscious thought theory (UTT: Dijksterhuis, 2004). UTT has encountered considerable censure with many studies failing to replicate the original findings. This study proposes that such appraisals are lacking in their consideration of problem type and distractor tasks. Three experimental conditions were used in the study: conscious, unconscious with differing distractor task, and unconscious with like-kind distractor task. Additionally, problem type manipulation was achieved through the presentation of two problem types (insight and analytic). Participants in the unconscious deliberation with similar distractor task condition achieved significantly higher solution rates than those in the conscious and unconscious deliberation with dissimilar distractor task conditions. No difference was found between the conscious and unconscious dissimilar task conditions. Notably, patterns were the same for both types of problems (insight and analytic). Thus, this study provided partial support for the UTT effect on both creative and analytic problem solving.